2016
DOI: 10.1016/j.ebiom.2016.06.032
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Circulating Tumor DNA for the Early Detection of Small-cell Lung Cancer

Abstract: Circulating tumor DNA (ctDNA) is emerging as a key potential biomarker for post-diagnosis surveillance but it may also play a crucial role in the detection of pre-clinical cancer. Small-cell lung cancer (SCLC) is an excellent candidate for early detection given there are no successful therapeutic options for late-stage disease, and it displays almost universal inactivation of TP53. We assessed the presence of TP53 mutations in the cell-free DNA (cfDNA) extracted from the plasma of 51 SCLC cases and 123 non-can… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
135
2
3

Year Published

2016
2016
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 165 publications
(143 citation statements)
references
References 41 publications
3
135
2
3
Order By: Relevance
“…Hence, we performed a new series of sequencing with an increase flow of 850 and detected a significant increase rate in coverage. This observation suggests to use other analytical variants, raising coverage until to 3000× in order to overcome troubles such as the reported low efficiency (24,32,33).…”
Section: Cancer Genomics and Proteomicsmentioning
confidence: 99%
“…Hence, we performed a new series of sequencing with an increase flow of 850 and detected a significant increase rate in coverage. This observation suggests to use other analytical variants, raising coverage until to 3000× in order to overcome troubles such as the reported low efficiency (24,32,33).…”
Section: Cancer Genomics and Proteomicsmentioning
confidence: 99%
“…This was shown in a recent study that used an assay specifically designed to accurately detect TP53 mutations at very low allelic fractions, in which cfDNA TP53 -mutated fragments were found in 11.4% of 123 matched non-cancer controls [70] (Fig. 1c).…”
Section: Mutation Baseline Value In Healthy Individualsmentioning
confidence: 56%
“…As an example, Fernandez-Cuesta and colleagues [12] recently used a pipeline specifically designed to accurately detect sequence variants present at very low fractions in cfDNA from patients with small-cell lung cancer (SCLC), addressing TP53 mutations, which are known to occur in the majority of cases of SCLC [13]. TP53 mutations were detected in only 35.7% of early-stage cases, indicating limited sensitivity as marker for detection of early SCLC.…”
Section: Cfdna In Patients With Early-stage Cancermentioning
confidence: 99%
“…Recent reports have shown that cancer-associated mutations are not restricted to cancer patients. For example, TP53-mutated cfDNA fragments were observed in 11.4% of 123 matched noncancer controls [12], and Krimmel and colleagues demonstrated very low levels of TP53 mutations in the peritoneal fluid and peripheral blood of women with benign ovarian lesions [14]. Likewise, leukemia-associated mutations have been shown to occur with increasing age and, although such mutations pose a statistically significant risk for a person to develop leukemia, most individuals (>90%) with these mutations never developed leukemia during their lifetime [15].…”
Section: Cancer-associated Mutations In Cancer-free Individualsmentioning
confidence: 99%